ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR PT. INDOFOOD SUKSES MAKMUR TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Sari, Dwi Maya (Universitas Mitra Indonesia, 2023)
After auditors conduct the audit assignment, the auditor should express an opinion on the fairness of the financial statements of a company that has been prepared in accordance with accounting principles generally accepted in Indonesia, to express an opinion on the audit report (audit report), however, if the assignment audit auditor found that there problems on the financial condition of the company that will have an impact on survival uncertainty (going concern, the company, the auditor is required to submit a statement of going concern audit opinion. opinion is a going concern modification to the audit opinion the auditor's consideration of problems the inability or uncertainty over the viability of the company. So with the statement of going concern audit opinion is expected to be a material consideration for the parties concerned on the financial statements, whether the company's internal and external, in making the right economic decisions. Based on these problems, the aim of this study was to examine and obtain empirical evidence about factors such as financial condition, the growth of the company, the previous year's audit opinion. To the possible influence of a going concern audit opinion. The process of selecting a sample using the method aims sample (purposive judgment sampling), so that the determination of the sample is determined. From the analysis of hypothesis testing using logistic regression models, so he found empirical evidence that financial conditions, growth of the company, the previous year's audit opinion positive effect on the going-concern audit opinion.